2010
DOI: 10.3844/jcssp.2010.1474.1478
|View full text |Cite
|
Sign up to set email alerts
|

Tone Question of Tree Based Context Clustering for Hidden Markov Model Based Thai Speech Synthesis

Abstract: Problem statement:In HMM-based Thai speech synthesis, tone is an important issue that brings about the intelligibility of the synthesized speech. Tone distortion resulted from imbalance of the training data should be appropriately treated. Approach: This study described an HMM-based speech synthesis system for Thai language. In the system, spectrum, pitch and state duration are modeled simultaneously in a unified framework of HMM, their parameter distributions are clustered independently by using a decision-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Both male and female speech has been constructed in the speech database. The extraction tools are applied in this study (Mixdorff and Fujisaki, 1997;Chomphan and Kobayashi, 2007a;2007b). For each parameter, the frequency distribution over its range is constructed, subsequently the distributions of standard Thai are plot in a graph.…”
Section: Resultsmentioning
confidence: 99%
“…Both male and female speech has been constructed in the speech database. The extraction tools are applied in this study (Mixdorff and Fujisaki, 1997;Chomphan and Kobayashi, 2007a;2007b). For each parameter, the frequency distribution over its range is constructed, subsequently the distributions of standard Thai are plot in a graph.…”
Section: Resultsmentioning
confidence: 99%
“…As for speaker dependent HMM-based Thai speech synthesis research, a speech synthesizer has been implemented (Chomphan and Kobayashi, 2007a). In the system, a group of contextual factors which affect spectrum, fundamental frequency (F0) and state duration, such as tone type and part of speech are taken into account especially for the purpose of producing natural sounding prosody of the tonal speech.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that it can provide speech with the better reproduction of prosody over the unit-selection-based Vaja TTS system from NECTEC (National Electronics and Computers Technology Center) (Chomphan and Kobayashi, 2007b). A decision tree with a toneseparated structure (Chomphan and Kobayashi, 2007a) presents the considerable improvement of tone correctness of the synthesized speech. However, some distortion of syllable duration is noticeable when the system is trained with a small amount of data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore appropriate predictive schemes for path-dependent connection-holding times will be required. Hidden Markov Model (HMM), provides the solution for wide variety of applications such speech tagging and noun-phrase chunking (Chomphan, 2012), is also flexible enough to predict any type of internet traffic (Dainotti et al, 2008) and has been demonstrated for wavelength assignment in WDM networks by Johnson et al (2001). In this study, we use thresholding of HMM predicted path-dependent connection holding times and show that this connection-time impairment aware provisioning of Burst Sizes and Associated Wavelength Allocation (ABS-WA) can reduce delays and improve throughput.…”
Section: Introductionmentioning
confidence: 99%